Model Kapabilitas Organisasi PENKUMMAS untuk Meningkatkan Reputasi Kejaksaan Tinggi Sumatera Selatan melalui Komunikasi Hukum Strategis - Sari, Vanny Yulia Eka; Alfitri, Alfitri; Thamrin, Husni; Lionardo, Andries (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to develop an organizational capability model based on the functions of Legal Information and Public Relations (PENKUMMAS) in enhancing the reputation of the South Sumatra High Prosecutor’s Office through strategic legal communication. Driven by increasing demands for transparency, accountability, and institutional legitimacy in public organizations, this research examines how legal communication functions as an instrument of reputational governance. Using a qualitative descriptive–interpretative approach, data were collected through in-depth interviews, observations, and document analysis involving officials and stakeholders within the South Sumatra High Prosecutor’s Office. The findings reveal that the PENKUMMAS function represents the organization’s adaptive capability in managing institutional reputation by applying the principles of dynamic capabilities (sensing, seizing, reconfiguring), combined with Fayol’s classical management theory and Grunig’s Excellence Theory. The resulting conceptual model, the Adaptive Reputational Capability Framework (ARCF), explains how public institutions can build and sustain reputation through strategic, responsive, and value-based legal communication. Practically, this model provides a framework for law enforcement agencies to strengthen their public communication functions as centers of institutional learning, transparency, and sustainable social legitimacy.